Specimen extraction and anvil placement methods in laparoscopic colorectal surgery: A single surgeon’s experience (Annals of Medical Research, 2021)
None
Keywords: Anvil Placement; Colectomy; Hemicolectomy; Low Anterior Resection; Natural Orifice Surgery